2008
DOI: 10.1348/135532507x218251
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity, reliability and predictive validity of the dynamic risk assessment and management system (DRAMS) in offenders with intellectual disability

Abstract: Background. There have been a number of developments in the assessment of dynamic risk in the criminological literature. The dynamic risk assessment and management system (DRAMS) has been developed to facilitate the measurement of dynamic factors of risk for offenders with intellectual disability. Method. The study was designed to assess the construct validity, reliability and predictive utility of the DRAMS in 23 male forensic patients in a high secure setting. Predictions were made against independently co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Jung et al for the concurrent validity of these HCR-20 measures (e.g. Righthand et al 2005;Steptoe et al 2008), but this has not always been the case (see Nunes and Babchishin 2011). Our findings show some support for the Historical and Clinical scales of the HCR-20 consistent with the findings of other studies (e.g.…”
Section: Journal Of Risk Research 707supporting
confidence: 86%
See 1 more Smart Citation
“…Jung et al for the concurrent validity of these HCR-20 measures (e.g. Righthand et al 2005;Steptoe et al 2008), but this has not always been the case (see Nunes and Babchishin 2011). Our findings show some support for the Historical and Clinical scales of the HCR-20 consistent with the findings of other studies (e.g.…”
Section: Journal Of Risk Research 707supporting
confidence: 86%
“…Juvenile Sex Offender Assessment Protocol' by Righthand et al 2005; 'Construct validity, reliability and predictive validity of the dynamic risk assessment and management system' by Steptoe et al 2008). Determining the construct validity of a test requires identification of the latent construct of interest and the integration of multifaceted evidence regarding the extent to which the test reflects that latent construct.…”
mentioning
confidence: 99%
“…; Steptoe et al . ). Dynamic measures also demonstrate moderate to high effect sizes in predicting sexual offending (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…() and Steptoe et al . () had already suggested that dynamic risk variables may be as good as or better than static variables in predicting violent and sexual incidents in offenders with intellectual disability. In this issue, Lofthouse et al .…”
Section: Introductionmentioning
confidence: 99%
“…Lofthous et al (2013) conducted an interesting analysis where they found that dynamic risk predictors may be act as a proxy for underlying static risk predictors. Lindsay et al (2004) and Steptoe et al (2008) had already suggested that dynamic risk variables may be as good as or better than static variables in predicting violent and sexual incidents in offenders with intellectual disability. In this issue, Lofthouse et al provide further evidence supporting these findings in relation to the perpetration of sexual offences.…”
Section: Introductionmentioning
confidence: 99%